The influence of the CEO's business education on the performance of hybrid organizations: the case of the global microfinance industry - D. Pascal; R. Mersland; N. Mori (Small Business Economics, 2017)
Microfinance institutions (MFIs) are typical examples of hybrid organisations, meaning organisations pursuing both a financial and social logic. This study examines the question of whether financial and social performance improves when an MFI's chief executive officer (CEO) has a business education. We apply the random effects instrumental variable regression method to examine the influence of the CEO's business education on the MFI's financial and social performance. Our panel dataset that includes 353 MFIs from across the globe indicates that `only' 55% of the MFIs have a CEO with a business education. The empirical results indicate that MFIs with CEOs who have a business education perform significantly better, financially and socially, than MFIs managed by CEOs with other types of educational backgrounds. The findings suggest that CEOs with a business education seem better at managing the much-debated tradeoff between providing small loans and producing healthy financial results.
Keywords: 650